Hospital‐based transfusion error tracking from 2005 to 2010: identifying the key errors threatening patient transfusion safety. Issue 1 (14th May 2013) - Maskens, Carolyn; Downie, Helen; Wendt, Alison; Lima, Ana; Merkley, Lisa; Lin, Yulia; Callum, Jeannie
<x xml:space="preserve">Abstract</x> Background This report provides a comprehensive analysis of transfusion errors occurring at a large teaching hospital and aims to determine key errors that are threatening transfusion safety, despite implementation of safety measures. Study Design and Methods Errors were prospectively identified from 2005 to 2010. Error data were coded on a secure online database called the Transfusion Error Surveillance System. Errors were defined as any deviation from established standard operating procedures. Errors were identified by clinical and laboratory staff. Denominator data for volume of activity were used to calculate rates. Results A total of 15, 134 errors were reported with a median number of 215 errors per month (range, 85‐334). Overall, 9083 (60%) errors occurred on the transfusion service and 6051 (40%) on the clinical services. In total, 23 errors resulted in patient harm: 21 of these errors occurred on the clinical services and two in the transfusion service. Of the 23 harm events, 21 involved inappropriate use of blood. Errors with no harm were 657 times more common than events that caused harm. The most common high‐severity clinical errors were sample labeling (37.5%) and inappropriate ordering of blood (28.8%). The most common high‐severity error in the transfusion service was sample accepted despite not meeting acceptance criteria (18.3%). The cost of product and component loss due to errors was 593, 337. Conclusion Errors occurred at every point in the transfusion process, with the greatest potential risk of patient harm resulting from inappropriate ordering of blood products and errors in sample labeling.